2021
DOI: 10.1186/s12885-021-08888-0
|View full text |Cite
|
Sign up to set email alerts
|

Nomogram to predict overall survival based on the log odds of positive lymph nodes for patients with endometrial carcinosarcoma after surgery

Abstract: Purpose Aims to compare the prognostic performance of the number of positive lymph nodes (PLNN), lymph node ratio (LNR) and log odds of metastatic lymph nodes (LODDS) and establish a prognostic nomogram to predict overall survival (OS) rate for patients with endometrial carcinosarcoma (ECS). Methods Patients were retrospectively obtained from Surveillance, Epidemiology and End Results (SEER) database from 2004 to 2015. The prognostic value of PLNN,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 35 publications
3
5
0
Order By: Relevance
“…A retrospective study had shown that LODDS was a superior predictive indicator for disease-free survival compared to pN and LNR in patients with rectal cancer [ 16 ]. Similar results and conclusions can be found in various studies with different cancers including lung squamous cell carcinoma [ 17 ], squamous cell carcinoma of the penis [ 18 ], colon cancer [ 19 ], endometrial carcinosarcoma [ 20 ], etc. For bladder cancer, Jin et al assessed the predictive capacity of pN, LNR, and LODDS in patients with muscle-invasive urothelial carcinoma of bladder cancer [ 12 ].…”
Section: Discussionsupporting
confidence: 88%
“…A retrospective study had shown that LODDS was a superior predictive indicator for disease-free survival compared to pN and LNR in patients with rectal cancer [ 16 ]. Similar results and conclusions can be found in various studies with different cancers including lung squamous cell carcinoma [ 17 ], squamous cell carcinoma of the penis [ 18 ], colon cancer [ 19 ], endometrial carcinosarcoma [ 20 ], etc. For bladder cancer, Jin et al assessed the predictive capacity of pN, LNR, and LODDS in patients with muscle-invasive urothelial carcinoma of bladder cancer [ 12 ].…”
Section: Discussionsupporting
confidence: 88%
“… 32 Compared with the above, LODDS could reflect both the absolute number of PLNs and negative LNs, indicating that it could stratify patients categorized as N0 classification (no regional LNM) and patients with all examined LNs metastasized. 29 , 33 , 34 …”
Section: Discussionmentioning
confidence: 99%
“…However, the association between LNR and tumor prognosis remains controversial when all or none examined LNs exhibited metastasis, especially with insufficient regional LNs removed 32 . Compared with the above, LODDS could reflect both the absolute number of PLNs and negative LNs, indicating that it could stratify patients categorized as N0 classification (no regional LNM) and patients with all examined LNs metastasized 29,33,34 …”
Section: Discussionmentioning
confidence: 99%
“…The rapid decline in mortality among men may be due in part to reduction in smoking ( 29 ). Thus, while medical advances have slowed the trend of rising mortality, targeted cancer control treatments remain urgent ( 11 , 25 , 27 , 28 , 30 ). Consistent with the overall rising incidence and slowing death trend, the prevalence of carcinosarcoma has increased year-by-year, mainly in women, elderly, blacks, and localized stage.…”
Section: Discussionmentioning
confidence: 99%
“…The total score was calculated using the quantitative score of each factor, and the 1-, 3-, and 5-year survival rate were scientifically and accurately predicted. Due to the inclusion of the primary tumor site, the predictive model is applicable to a wider population of patients and has a better predictive probability than other single-site predictive models ( 11 , 30 ). In summary, this simple but effective model could be used to individualize prognostic assessment of carcinosarcoma and will facilitate clinical decision-making.…”
Section: Discussionmentioning
confidence: 99%